Determination of coagulopathy complicating severe preeclampsia and eclampsia with platelet count - Jayashree, Venkata; Renuka, Lakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Preeclampsia is a dangerous complication which occurs potentially in pregnancy and is characterised by high blood pressure. It effects maternal and perinatal health and is complicated by abnormalities of coagulation. The aim of the study was to determine platelet count which predicted coagulopathy in patients with severe preeclampsia and eclampsia. Methods: Prospective cohort study done in all patients were admitted with diagnosis of severe preeclampsia and eclampsia and admitted for stabilisation. Blood samples were collected from all patients for detecting bleeding, clotting time, electrolytes, urea and creatinine, liver functions tests, full blood count, platelet count, prothrombin time, activated partial thromboplastin time and plasma fibrinogen level in 100 patients in total. Using chi square test, univariate analysis was conducted. Results: Out of 100 women patients, 70 (70%) patients had severe preeclampsia and 30 (30%) patients had eclampsia out of which 15 patients had thrombocytopenia. The incidence of thrombocytopenia among patients was 16.6%. Biochemical coagulopathy was noted in 7%. Patients with severe preeclampsia had platelet count of 185000±61289 per µl, PT was 13.52±1.48 sec, APTT was 34.52±2.49 sec and fibrinogen was 3.16±0.22 g/dl. Patients with eclampsia (with thrombocytopenia) had platelet count of 79528±14897 per µl, PT was 19.25±5.28 sec, APTT was 37.08±5.33 sec and fibrinogen was 2.67±0.53 g/dl. Thrombocytopenia was complicated with eclampsia and it was associated with biochemical coagulopathy which made the condition more severe. Conclusions: 80000 cells/µl is the thrombocytopenia level which is considered to be critical in severe preeclampsia and eclampsia. This will help to reduce maternal and perinatal mortality and morbidity rates.